Citizen in Sensor Networks Second International Workshop, CitiSens 2013, Barcelona, Spain, September 19, 2013, Revised Selected Papers - Nin, Jordi; Villatoro, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the proceedings of the Second International Conference on Citizen Sensor Networks, CitiSens 2013, held in Barcelona, Spain, in September 2013. The 8 papers presented in this volume were carefully reviewed and selected from 16 submissions. The topics covered are: trajectory mining, smart cities, multi-agents systems, networks simulation, smart sensors and clustering or data anonymization.
Trajectory Mining -- Actions in Context: System for people with Dementia -- Transportation planning based on GSM traces: a case study on Ivory Coast -- From Tweets to Semantic Trajectories: mining Anomalous Urban Mobility Patterns -- Transportation Networks -- Crowdsensing Simulation Using ns-3 -- On the Use of Social Trajectory-based Clustering Methods for Public Transport Optimization -- Migration Movements -- Tracking Human Migration From Online Attention -- Data Anonymization -- Beyond Multivariate Microaggregation for Large Record Anonymization.
Keywords: Computer science; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computer Applications